Urgensi Mata Kuliah Tata Kelola Koleksi Museum dalam Meningkatkan Kompetensi Mahasiswa Ilmu Perpustakaan UINSU - Ardilla, Shintia Wanna; Siregar, Yusra Dewi (Ideas Publishing, 2024)
Libraries and museums are two cultural institutions that have a vital role in preserving, disseminating and interpreting cultural heritage and human knowledge. In this context, museum governance is a key aspect that influences learning effectiveness. The aim of this research is to determine the existence of museum management courses in improving student competency and what is the relationship between this course and the graduation profile of library science students. The method used is descriptive qualitative, using observations and interviews as data collection. The research results show that learning related to museum collection management provides a deep understanding of collection and information management. The implication of this finding is that courses related to museum management are closely related to library science, one of which is collection management and information management.